The Dynamics Of Contemporary Islamic Education: Between Tradition, Modernization, And Innovative Learning Approaches - Utama, Abdul Alimun; Hidayati, Sri Wahyu (Jurnal Ilmiah Mandala Education (JIME), 2026)
Islamic education plays a strategic role in shaping students’ character, faith, and intellectual development. Along with the rapid changes brought by globalization, technological advancement, and social transformation, Islamic education faces new challenges that require continuous adaptation. This article aims to examine the dynamics of contemporary Islamic education by focusing on the relationship between educational traditions, modernization processes, and innovative learning approaches. This study employs a qualitative approach using library research, drawing data from national journals, academic books, and other relevant scholarly sources. The findings indicate that the modernization of Islamic education is an adaptive process that remains rooted in Islamic values rather than a form of westernization. Furthermore, innovative learning approaches such as project-based learning, problem-based learning, and the use of digital media can enhance the quality of Islamic education when they are oriented toward strengthening the internalization of Islamic values. This study is expected to provide a conceptual contribution to the development of relevant and sustainable Islamic education in the modern era.